Clinical outcomes of postpartum intrauterine devices inserted by midwives in Tanzania. (18th September 2018) - Muganyizi, Projestine S.; Kimario, Grasiana; Ponsian, Patrick; Howard, Kate; Sethi, Maya; Makins, Anita
Abstract: Objective: To assess the rate of complications following immediate postpartum insertion of intrauterine devices (IUDs) by trained midwives in Tanzania. Methods: A prospective cohort study of women who underwent immediate postpartum IUD (PPIUD) insertions provided by midwives between December 31, 2016 and October 15, 2017. Midwives received standardized training via the FIGO initiative. Women who returned 6 weeks after delivery were evaluated for complications. Outcomes of interest were uterine infection, IUD expulsion, medical removal of IUD, and method discontinuation. Results: There were 40 470 deliveries, 2347 (5.8%) PPIUD insertions, and 1013 (43.2%) women with a PPIUD who returned for a follow‐up visit in the program‐affiliated clinics. Midwives were providers in 596 (58.8%) of these follow‐up cases and clinicians in 417 (41.2%) cases. All PPIUD insertions by midwives were transvaginal and among them 43 (7.2%) had PPIUD‐related complications by the end of sixth week. These complications included 16 (2.7%) cases of uterine infection, 14 (2.3%) IUD expulsions, 26 (4.4%) IUD removals, and 33 (5.5%) with overall method discontinuation. Only one case had uterine infection severe enough to warrant hospitalization. Conclusion: PPIUD insertion by trained midwives in Tanzania compares favorably with results reported from other settings. Abstract : When trained to insert intrauterine devices immediately postpartum, midwives can access more clients with favorable outcomes.